Handgrip Maximal Voluntary Isometric Contraction Does Not Correlate with Thenar Motor Unit Number Estimation - Arun Aggarwal (Neurology Research International)
In slowly progressive conditions, such as motor neurone disease (MND), 50–80% of motor units may be lost before weakness becomes clinically apparent. Despite this, maximal voluntary isometric contraction (MVIC) has been reported as a clinically useful, reliable, and reproducible measure for monitoring disease progression in MND. We performed a study on a group of asymptomatic subjects that showed a lack of correlation between isometric grip strength and thenar MUNE. Motor unit number estimation (MUNE) estimates the number of functioning lower motor neurones innervating a muscle or a group of muscles. We used the statistical electrophysiological technique of MUNE to estimate the number of motor units in thenar group of muscles in 69 subjects: 19 asymptomatic Cu, Zn superoxide dismutase 1 (SOD 1) mutation carriers, 34 family controls, and 16 population controls. The Jamar hand dynamometer was used to measure isometric grip strength. This study suggests that MUNE is more sensitive for monitoring disease progression than maximal voluntary isometric contraction (MVIC), as MUNE correlates with the number of functional motor neurones. This supports the observation that patients with substantial chronic denervation can maintain normal muscle twitch tension until 50–80% of motor units are lost and weakness is detectable.